Precipitate synthesis of BaMoO4and BaWO4nanoparticles at room temperature and their photoluminescence properties - Anukorn Phuruangrat (2018)
The uniform BaMoO4and BaWO4nanoparticles (NPs) have been successfully synthesized by solution route - the direct precipitation of Ba(NO3)2and Na2MO4(M = Mo and W) in ethylene glycol under 24 h stirring. The XRD patterns and SEM images proved that the products were tetragonal structured BaMoO4and BaWO4with uniform round nanoparticles. Shape, average particle size and particle-size distribution of products were analyzed by TEM - showing the round nanoparticles with the average size of 31.52 ± 4.65 nm for BaMoO4, and 59.77 ± 9.61 nm for BaWO4. The room temperature photoluminescence (PL) indicated that the products have strong blue emission centered at 441 nm - excited with 280 nm wavelength for BaMoO4NPs, and strong violet emission centered 378 nm - excited with 344 nm wavelength for BaWO4NPs. These PL behaviors attributed the existence of intrinsic transitions in the [MO4]2-(M = Mo and W) tetrahedrons of their crystal lattices. © 2012 Elsevier Ltd. All rights reserved.